Acoustic measurements and intelligibility of English vowels produced by Thai speakers - Kamonnate Iadkert; Roshidah Hassan; Azirah Hashim (Studies in English Language and Education)
Effective English communication across different languages and cultures has become increasingly important in a globalised world. To gain a deeper understanding of the segmental features of Thai speakers of English, this study aims to investigate the production of English monophthongs and diphthongs by Thai speakers and examine how intelligible their pronunciations are to others. Data were collected through two tasks: a production task and a listening task. For the production task, three Thai female speakers were chosen as the participants. They were recorded reading a passage consisting of all targeted vowels, and a total of 180 English tokens were analysed. For the listening task, thirty Malaysian listeners were asked to evaluate the speech intelligibility of the English sounds produced by the three speakers. The duration and formant frequencies of English vowels produced were measured to investigate the characteristics of the monophthongs and diphthongs. The findings show that there were significant differences in the durations between long and short vowels of the monophthongs, but there were no significant differences in the vowel quality produced. The ROC (rate of change) of formant frequencies (F1 and F2) indicates that there was no formant movement for the diphthongs /eɪ/, /əʊ/, and /eə/. The three diphthongs showed similar characteristics as other ASEAN Englishes that are monophthongal as /e:/, /o:/, and /ɛ:/, respectively. These findings confirm that speakers’ L1 influences English vowel production. Although there were vowel variations in the characteristics of the vowels produced by the speakers, the intelligibility scores were high.